Емкостные свойства МДП-структур HgCdTe/SiO2/Si3N4 - Voitsekhovskii, A. V.; Nesmelov, S. N.; Kulchitskii, N. A. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The capacitance–voltage characteristics of n(p)-HgCdTe/SiO2/Si3N4 and n(p)-HgCdTe/anodic oxide film MIS structures have been experimentally investigated at different frequencies and voltage sweep directions. Specific features of electrophysical characteristics have been identified, associated with the bulk resistance of the epitaxial film and the presence of near-surface variband layers. It has been shown that the use of a two-layer dielectric SiO2/Si3N4 is promising for surface passivation of matrix HgCdTe photodiodes for the infrared range.